Penguatan Bahasa Indonesia Sebagai Lambang Identitas Nasional - Chandra Fauzy; Dimas Reza Febrian; Muhammad Fahmi Ramadhan (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The purpose of this research is to analyze the strengthening of the Indonesian language in the country of Indonesia as a symbol of national identity. The writing method used in this research is descriptive-qualitative method. Type of data, The type of data used in this research is secondary data collected from various literatures using the theoretical basis, namely national identity in strengthening the Indonesian language. Indonesian has been designated as a language of unity and a symbol of national identity in the law and national linguistic conferences. Language is one of the national identities. Indonesian is the national identity of the Indonesian people. Language is used as a means of communication between communities. Not only as a means of communication language is also made as a national identity. Although there are many languages in Indonesia, Indonesian is able to unite 1128 ethnic groups with 746 regional languages united by one language, namely Indonesian. It is hoped that the Indonesian language can foster a sense of nationalism towards the nation and state. As the phenomenon at this time a lot of use of English shows that Indonesians forget their original identity. With the growing sense of nationalism in Indonesian society with the use of Indonesian, the Indonesian language will be stronger as the national identity of the Indonesian people. National identity is a form of identity of a country to distinguish a country from other countries. Language is one of the national identities. Indonesian is the national identity of the Indonesian people. Language is used as a means of communication between communities. Not only as a means of communication language is also made as a national identity. Although different ethnicities, cultures, religions but Indonesia is united with one language, namely Indonesian. It is hoped that the Indonesian language can foster a sense of nationalism towards the nation and state. With the growing sense of nationalism in Indonesian society with the use of the Indonesian language, the Indonesian language will be stronger as the national identity of the Indonesian people.